Biomaterial‐Associated Persistence ofStaphylococcus epidermidisin Pericatheter Macrophages - Jaap Jan Boelens; J. Dankert; Jean‐Luc Murk; Jan J. Weening; Tom van der Poll; K. P. Dingemans; Léo H. Koole; Jon D. Laman; Sebastian A. J. Zaat (2000)
Biomaterial surfaces may be modified to reduce bacterial adhesion. The susceptibility in mice to Staphylococcus epidermidis infection in tissue surrounding the commonly used catheter materials-silicon elastomer (SE), polyamide (PA), and their surface-modified polyvinylpyrrolidone (PVP)-grafted derivatives, SE-PVP and PA-PVP, respectively-was assessed. Abscesses developed around SE-PVP. Around SE, PA, and PA-PVP catheters, no signs of infection were observed, although mice carrying PA-PVP developed septicemia after 14-21 days. S. epidermidis was cultured from the tissue surrounding PA-PVP segments. Cells around PA-PVP segments containing large numbers of bacteria were identified as macrophages by use of immunohistochemistry and electron microscopy. This persistence of intracellular bacteria was also observed around SE-PVP, SE, and PA catheters, although to a lesser extent. The cytokine profiles around the 4 materials were different. Implanted biomaterial induces an inflammatory response favorable to the persistence of S. epidermidis. Intracellular persistence of bacteria inside macrophages may be a pivotal process in the pathogenesis of biomaterial-associated infection.